Prototipe Buku Cerita Anak Berbasis Budaya Lokal Melalui Analisis Sikap dan Muatan Pembelajaran Tema Ekosistem Kurikulum 2013 Kelas V Sekolah Dasar - Laili Alfi Rahmatin; Made Ayu Pransisca (Jurnal Ilmiah Wahana Pendidikan, 2020)
This research aims to analyze and describe the behavioral values and content of science learning as well as the local cultural potential of its support in the curriculum 2013 in the theme of Ecosystem at the fifth grade of elementary school. The reasearch was conducted under descriptive qualitative design. The data analysis were done by using descriptive qualitative. The subject of this research are cultural observer, teacher of grade 5 elementary school, SBdP teacher, ande the parents of grade 5 students. The research toward teachers and students book about Ecosystem reveals that: (1) the spiritual behaviors which appear are the obedience of worship (2) the social behaviors which appear are being honest, discipline, responsible, well mannered, care and having self-confidence. (3) The content of science learning that apper are the environment, the univers, and natural resources. (4) the local cultural values which appear in the higher class activities that support the development of behavioral values in Ecosystem theme are, some traditional games, kids story (waran), singing (melawas), greeting, and obligation to pray. Furthermore, the result of this research reveals prototype kids book stories based on local culture in the theme of Ecosystem in grade 5 elementary school.